Bungo stray dogs. 01 - Asagiri, Kafka (New York : Yen Press, 2023)
Not long after Ougai Mori takes the reins of the Port Mafia, he orders a young Osamu Dazai to investigate an ominous rumor of something called "Arahabaki." Whoever or whatever it is seems to have some connection to Mori's deceased predecessor--and the new boss would very much like for the dead to stay buried. Along the way, Dazai runs into a gravity manipulator named Chuuya Nakahara, leader of the Sheep gang of youths. Together, the two will one day achieve infamy as the fearsome duo known as Twin Dark, but for now, they'll have to learn to put aside their differences if they want to get to the bottom of this mystery...